2007
DOI: 10.1063/1.2429656
|View full text |Cite
|
Sign up to set email alerts
|

Probing the O2 (aΔg1) photofragment following ozone dissociation within the long wavelength tail of the Hartley band

Abstract: The technique of resonance enhanced multiphoton ionization (REMPI) has been used in conjunction with time-of-flight mass spectrometry (TOFMS), to investigate the dynamics of ozone photolysis in the long wavelength region of the Hartley band (301-311 nm). Specifically, both the translational anisotropy and the rotational angular momentum orientation of the O(2) (a (1)Delta(g); nu=0, J=16-20) fragments have been measured as a function of photolysis wavelength. Within this region, the thermodynamic thresholds for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In this region, the above mechanism is superseded by the cold band production of O( 1 D) in the spin-forbidden channel 4. Spin-forbidden dissociation in the Huggins band is well-characterized experimentally. ,,, These studies, focused on the “tail of the tail” region of 325 nm ≤ λ ≤ 340 nm, detected pronounced peaks in the high resolution yields and bounded the average yield between 0.06 , and 0.08 or 0.12 . Yields of about 0.1 were also observed for the spin-forbidden channels 2 and 3, producing O( 3 P). , Dynamical aspects of the spin-forbidden dissociation remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this region, the above mechanism is superseded by the cold band production of O( 1 D) in the spin-forbidden channel 4. Spin-forbidden dissociation in the Huggins band is well-characterized experimentally. ,,, These studies, focused on the “tail of the tail” region of 325 nm ≤ λ ≤ 340 nm, detected pronounced peaks in the high resolution yields and bounded the average yield between 0.06 , and 0.08 or 0.12 . Yields of about 0.1 were also observed for the spin-forbidden channels 2 and 3, producing O( 3 P). , Dynamical aspects of the spin-forbidden dissociation remain poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism, dating back to the model calculations of Adler-Golden et al, suggests that tiny Boltzmann populations of some states (υ 1 , υ 2 , υ 3 ) X are counterbalanced by a strong increase in the absorption from these states. Photofragment vector correlations measured in channel 5 indicate that transitions from vibrationally excited states are responsible for ∼30% of Φ O1D at 308 nm and for ∼100% at 311 nm . The temperature-independent component of Φ O1D at λ > 320 nm is sharply structured at high resolution, as demonstrated by the jet-cooled photofragment excitation spectra .…”
Section: Introductionmentioning
confidence: 87%
“…While many investigators have studied the fall-off of the quantum yield for O( 1 D)+ O 2 ( a 1 Δ g ) starting at 310 nm, , O’Keeffe et al were the first to show the complexity of other product channels in the ozone dissociation wavelength range above 320 nm. These include: .25ex2ex normalO 3 normalO 2 ( X Σ g 3 ) + normalO ( P 3 ) ( 1 ) infix→ normalO 2 ( a 1 Δ g ) + normalO ( P 3 ) ( 2 ) infix→ normalO 2 ( b Σ + g 1 ) + normalO ( P 3 ...…”
Section: Introductionmentioning
confidence: 99%
“…This velocity dependence was confirmed and characterized for a wide range of N in v = 0, for both 248 and 266 nm photolysis, by Costen and Hall using FM Doppler spectroscopy [7], These experiments demonstrated that single rotational levels of CN produced in the I and I* channels did indeed have opposite orientations, and that both the integral and Doppler-resolved orientations could be described by a single parameter. [38][39][40]. The molecular frame orientation in these systems integrates to zero in the laboratory frame, and is undetectable with one-photon Doppler absorption spectroscopy, although it can be observed with REMPI time-of-flight, Doppler-resolved LIF with polarization analyzed emission, or ion-imaging methods.…”
Section: Introductionmentioning
confidence: 99%